Literature, mapping, and the politics of space in early modern Britain: [... conference organised by the editors at Queen Mary and Westfield College, University of London, in July 1997 under the title "Paper landscapes: maps, texts, and the construction of space, 1500 - 1700"] - Gordon, Andrew; Klein, Bernhard (Cambridge University Press, 2001)
Absorption and representation: mapping England in the early modern House of Commons / Oliver Arnold -- A map of greater Cambria / Philip Schwyzer -- Britannia rules the waves?: images of empire in Elizabethan England / Lesley B. Cormack -- Performing London: the map and the city in ceremony / Andrew Gordon -- Visible bodies: cartography and anatomy / Caterina Albano -- The scene of cartography in King Lear / John Gillies -- Unlawful presences: the politics of military space and the problem of women in Tamburlaine / Nina Taunton -- Marginal waters: Pericles and the idea of jurisdiction / Bradin Cormack -- 'On the Famous Voyage': Ben Jonson and civic space / Andrew McRae -- Imaginary journeys: Spenser, Drayton, and the poetics of national space / Bernhard Klein -- Do real knights need maps? Charting moral, geographical and representational uncertainty Edmund Spenser's The Faerie Queen / Joanne Woolway Grenfell -- The folly of maps and modernity / Richard Helgerson